2003
DOI: 10.1021/bp0341186
|View full text |Cite
|
Sign up to set email alerts
|

Improved Mammalian Expression Systems by Manipulating Transcriptional Termination Regions

Abstract: Here we show that the transcriptional terminator element of human gastrin gene, which is the only element characterized to date in terms of its function in transcriptional termination, increases the transient expression levels of recombinant proteins. The expression of the beta-galactosidase gene was enhanced 3-4-fold in HeLa cells by inserting the terminator element of human gastrin gene at the 3'-side of the SV40 polyadenylation signal/cleavage site of the control vector (pSV-beta-gal). This effect of the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For example, linking various elements of UAS GAL to a constitutive core results in a functional, galactose inducible promoter [51]. A similar approach has been conducted with regulated regions of the ARO9 UAS [58]. Collectively, these approaches resulted in a library of galactose-inducible promoters with a 40-fold range in induced expression strength, and a tryptophan-inducible promoter with a 29-fold range in induced expression strength.…”
Section: Hybrid Promoter Engineeringmentioning
confidence: 99%
“…For example, linking various elements of UAS GAL to a constitutive core results in a functional, galactose inducible promoter [51]. A similar approach has been conducted with regulated regions of the ARO9 UAS [58]. Collectively, these approaches resulted in a library of galactose-inducible promoters with a 40-fold range in induced expression strength, and a tryptophan-inducible promoter with a 29-fold range in induced expression strength.…”
Section: Hybrid Promoter Engineeringmentioning
confidence: 99%
“…The viral CMV promoter and the promoters of mammalian elongation factor 1-alpha (EF1a) and actin genes are routinely used for expression [8][9][10][11]. The following terminators are often used: viral SV40, b-globin, and BGH [12][13][14][15]. In addition, genes are often fused inframe with short epitope tag sequences, such as FLAG, Myc, HA, and V5, at their 5 0 -or 3 0 -terminus to utilize immune detection assays [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The modularity and portability of terminators in mammalian cells has been evaluated in a study that investigated the endogenous human gastrin gene element along with the viral SV40 terminator and affirmed improved reporter gene expression in three tested mammalian cell lines . As a result, this work suggested that mammalian host terminators can be rationally designed in a similar fashion to yeast , for improved translational output.…”
mentioning
confidence: 99%